(untitled) (Quinto Sol, 2011)
In Argentina, Social Sciences have read the 20th Century Family History through an interpretative model, which has received a multiplicity of names, and which we will call “classic model”. In this article, our major aim is to reach a more complex image of the family life of the period in which this model is considered predominant (between the 1930’s and the 1970’s), one that acknowledges both the permanence of the bonds with relatives out of the nuclear family, and the conflicts that are inherent to family life. That is the reason why we work with life stories, making emphasis in everyday life experiences. The relation between family and household –the perspective from where we propose to approach the family history- is an interesting entrance for the consideration of central problems of Family Studies field.